DIMANTRA: LINGUAL-TACTUAL SENSORY MEDIA FOR BALI BLIND TOURISM - Dewa Ayu Dyah Pertiwi Putri; I Gusti Ngurah Adi Rajistha; Dewa Ayu Kadek Claria (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2020)
This research aims to design an effective media—Dimantra—to support blind tourism in Bali. The media is intended to help blind tourists to visualize objects and atmosphere in a tourist attraction through lingual narration in the form of audio, equipped with tactual three-dimensional miniatures of the tourist attraction. The theory used in this research was the types of narrative, especially suggestive narrative by Keraf. The method used in collecting data to create the narration audio was observation method supported by note taking technique. Meanwhile, the method used in collecting data related to the effectiveness of Dimantra was interview method supported by closed questionnaire. The results showed that the effective narrative formulation in building visual sensations for blind people was general-specific narrative supported by informative, communicative, and detailed sentences in terms of positions, distances (measurements), directions, textures, and colors. Meanwhile, the effective materials to create proper three-dimensional miniature were newspapers covered with real or semi-real materials such as soft sands to convey beach, hard sands to form rocks, and wet cottons to convey water. Further, Dimantra was considered to be effective in helping blind people to visualize tourist attraction based on the percentage of samples’ responses, namely 53% strongly agree that Dimantra was effective, 37% agree, 5% neutral, and 0% disagree or strongly disagree.